Sustainable management and comprehensive administrative control of asphalt pavements case study, Perú - Lopez Almeida, Mercedes Evangelina (2023)
The management of asphalt pavements is of great importance for the development of road, motorway and airport runway infrastructures. For the company to achieve its goals, the use of administrative control instruments or tools such as evaluations and follow-ups of employees. Such control begins with the design by the company of an organizational structure where activities are planned and their effectiveness with their subsequent evaluations. The study aimed to analyze the management of asphalt maintenance and its administration process in a pavement and construction company in the Lima region, Peru. The methodology used was the hypothetical deductivo. Thedesign was non-experimental and cross-sectional deliberating the variables in a single time of study in a descriptive way, the sample population was the administrative workers and workers to perform the research technique, the type of instrument used was the survey with anonymous questions and closed questions, or at least all those questions that best respond to the situation we want to know. An analysis of frequencies and weighting of percentages was made from which it obtained, the values that allowed us to know the problems of the company with respect to the variables under study such as administrative control and maintenance, the validity of the instrument had a degree of reliability of Cronbach's alpha of 0.879 for the variable Administrative control and maintenance of 0.849. In the research regarding the dimensions of asphalt pavement have a relationship with the administrative management of the company, having a positive significance.